Comparative determinants of horse-race coverage. (17th January 2014) - Banducci, Susan; Hanretty, Chris
Abstract : We investigate the levels of horse-race coverage in 160 different European print and broadcast outlets in 27 different countries at three different points in time. We match information on outlets' content to survey-based information on the average levels of interest in politics and education of outlets' audiences. We formulate hypotheses concerning journalists' and citizens' preferences over the ideal level of horse-race coverage, as well as hypotheses concerning the information content of horse-race coverage in different party systems. After controlling for the composition of each outlet's audience, we find that horse-race coverage is most frequent in polarized party systems with close electoral contests, and in large markets with professional journalists. These findings challenge the traditional view of horse-race journalism as a 'low-quality' form of news.